2015
DOI: 10.1364/boe.6.001942
|View full text |Cite
|
Sign up to set email alerts
|

Accurate real-time depth control for CP-SSOCT distal sensor based handheld microsurgery tools

Abstract: This paper presents a novel intuitive targeting and tracking scheme that utilizes a common-path swept source optical coherence tomography (CP-SSOCT) distal sensor integrated handheld microsurgical tool. To achieve micron-order precision control, a reliable and accurate OCT distal sensing method is required; simultaneously, a prediction algorithm is necessary to compensate for the system delay associated with the computational, mechanical and electronic latencies. Due to the multilayered structure of retina, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 46 publications
0
30
0
1
Order By: Relevance
“…The Kang group at Johns Hopkins University demonstrated that Ascans could be acquired adjacent to the tooltip by mounting a fiber-optic common-path (CP) OCT probe along [107,108] or within [109][110][111] the shafts of forceps and needles for vitreoretinal surgery (Fig. 3(a)).…”
Section: Oct-integrated Surgical Instrumentsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Kang group at Johns Hopkins University demonstrated that Ascans could be acquired adjacent to the tooltip by mounting a fiber-optic common-path (CP) OCT probe along [107,108] or within [109][110][111] the shafts of forceps and needles for vitreoretinal surgery (Fig. 3(a)).…”
Section: Oct-integrated Surgical Instrumentsmentioning
confidence: 99%
“…The reference interference signal was obtained from the partial back-reflection at the distal surface of the CPOCT probe, and the lack of an optical scanning mechanism resulted in a relatively simple and affordable optical design that could potentially be made as a disposable product. In its most recent iteration [108], the probe used a 100 kHz swept-source with a 1060 nm central wavelength, and M-scan images could be acquired and processed with GPU-accelerated software. The OCT probe was primarily used as a single-point axial ranger with micrometer-scale resolution to quantify hand tremor [111] and drive active motion cancellation systems [107,108,110], and to provide ranging feedback for a cooperative robotic surgery platform [109] (discussed in detail in Section 5.2).…”
Section: Oct-integrated Surgical Instrumentsmentioning
confidence: 99%
See 3 more Smart Citations